Evaluation of Mining Sector Tax Collection Performance from the Perspective of Regional Fiscal Management - M. Rudin; Maria Lea Frensy Bakarbessy (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Local revenue is a primary source of funding for development at the local level, one of which is through the collection of Non-Metallic Mineral and Rock (Mineral Bukan Logam dan Batuan/MBLB) taxes. This study aims to analyze the effectiveness of the collection of Group C MBLB taxes in Palu City and to identify the supporting and inhibiting factors in the tax collection process. The research method used is a quantitative study with a descriptive-analytic approach, utilizing secondary data from the Regional Revenue Agency of Palu City and limited interviews with relevant staff. Data analysis focuses on calculating the effectiveness level of tax collection and evaluating the factors that influence target achievement. The results show that the effectiveness of Group C MBLB tax collection in Palu City during the period 2019 to 2022 was categorized as highly effective, but it declined to a less effective category in 2023. Key supporting factors include a strong legal basis, investment growth, adequate supporting facilities, and an integrated online payment system. On the other hand, limitations in human resources, lack of taxpayer understanding of online payment procedures, inaccurate taxpayer data, and complex bureaucracy are significant obstacles.